Oxidative and Microbiological Profiles of Chicken Drumsticks Treated with Ultraviolet‐C Radiation. Issue 6 (7th July 2015) - Cichoski, Alexandre J.; Moura, Heloísa C.; Silva, Marianna S.; Rampelotto, Cristine; Wagner, Roger; Barin, Juliano S.; Vendruscolo, Raquel G.; Dugatto, Jonas S.; Athayde, Dirceu R.; Dalla Costa, Marco A.
Abstract: The effect of ultraviolet‐C (UV‐C) radiation (doses of 5.4 and 9.46 kJ/m 2 ) on microbiological and lipid and protein oxidation of chicken drumsticks was evaluated at different temperatures of application (5 and 25C). Products were stored 12 days at 5C, showing a reduced number of total aerobic and psychrotrophic bacteria ( P  < 0.05) along almost all storage period for products treated with UV‐C. However, the same effect was not observed for yeasts and molds. Samples treated at 25C presented lower amount of polyunsaturated fatty acid (PUFA) n ‐6 and n ‐3 and higher levels of conjugated diene (CD) ( P  < 0.05) than those treated at 5C. The results suggested the application of UV‐C at 5C to provide a lower number of total aerobic and psychrotrophic bacteria with higher levels of PUFA and lower levels of CD. Practical Applications: There are only a few information about the impact of UV‐C radiation on chicken food treated with different UV intensities and temperatures of application. In this way, a microbiological and lipid and protein oxidation study was performed showing the influence of these parameters on chicken drumsticks treated with ultraviolet‐C radiation.